Sistem Pendukung Keputusan Pemilihan Paket Kartu Perdana Untuk Kebutuhan Daring Selama Masa Pandemi Dengan Metode AHP (Analytical Hierarchy Process) Berbasis Web (Studi Kasus: Perumahan Taman Alamanda) - Gilang Rakasiwi; Achmad Udin Zailani (CV. Multi Kreasi Media, 2024)
In the midst of the COVID-19 pandemic, learning and work activities cannot be carried out directly in order to reduce the spread of the virus so that the need for online activities used in work from home and school from home are increasing for all groups of people. To meet these online needs, the government has tried to provide internet assistance packages to the community. Of course, the assistance provided by the government is very limited so many people need additional internet packages to meet their individual needs. SIM card is a product that can be used for mobile phone users and internet modem to connect to the Internet through a provider they choose. Most people use SIM cards for internet access services, especially for people who do not have access to cable internet, either because it is outside the reach of the provider or because of cost constraints. The choices for SIM cards are numerous and varied with different packages and features, so that potential users will be faced with the question of which SIM card is the best for their individual needs. To answer that question, the decision support system for choosing a SIM card for online needs is expected to assist in determining the best SIM card according to the criteria of each user. The results of this study will show the implementation of the Analytical Hierarchy Process (AHP) method in the process of assessing and selecting the best SIM card.